Effects of concurrent training sequence on VO2max and lower limb strength performance: A systematic review and meta-analysis - Gao, Jiuxiang; Yu, Liang (Frontiers in Physiology, 2023)
To compare the effect of concurrent strength and endurance training sequence on VO2max and lower limb strength performance to provide scientific guidance for the training practice. We searched Pubmed, EBSCO, Web of science (WOS), Wanfang and China National Knowledge Infrastructure (CNKI) databases up to December 2022. Included articles were randomized controlled trials that allowed to compare between the strength-endurance (S-E) sequence and endurance-strength (E-S) sequence on VO2max, maximum knee extension strength, maximum knee flexion strength and lower limb power. Cochrane bias risk tool was used to evaluate the methodological quality of the included literature, and Stata12.0 was used for heterogeneity test, subgroup analysis, draw forest map, sensitivity analysis, and publish bias evaluation. Results were presented as standardized mean differences (SMDs) between treatments with 95% confidence intervals, and calculations were performed using random effects models. Significance was accepted when P<0.05. The studies included in the analyses 19 randomized controlled trials (285 males, 197 females), 242 subjects in S-E sequence and 240 subjects in E-S sequence. No difference changes between S-E and E-S sequences is observed on VO2max in overall analysis (SMD=0.02, 95%CI: -0.21-0.25, P=0.859). S-E sequence showed a greater increase in lower limb strength performance than E-S sequence (SMD=0.19, 95%CI: 0.02-0.37, P=0.032), which is manifested in the elderly(P=0.039), women (P=0.017), training period >8 weeks (P=0.002), training frequency twice a week (P=0.003), maximum knee flexion (P=0.040), knee extension strength (P=0.026) and no difference was found in lower limb power (P=0.523); In conclusion, concurrent training sequence will not affect the change of VO2max. The S-E sequence improves lower limb strength more significantly, mainly in the improvement of knee flexion and knee extension. This advantage is more related to factors such as age, gender, training period, and training frequency.